2010
DOI: 10.1111/j.1750-2659.2010.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Original Article: Assessing physicians’ in training attitudes and behaviors during the 2009 H1N1 influenza season: a cross‐sectional survey of medical students and residents in an urban academic setting

Abstract: Please cite this paper as: May et al. (2010) Assessing physicians’ in training attitudes and behaviors during the 2010 H1N1 influenza season: a cross‐sectional survey of medical students and residents in an urban academic setting. Influenza and Other Respiratory Viruses DOI: 10.1111/j.1750‐2659.2010.00151.x. Background  Despite concern for hospital‐based transmission of influenza, little research has been carried out on perceptions and behaviors of physicians in training with regard to influenza‐like illness (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(68 citation statements)
references
References 29 publications
3
61
1
3
Order By: Relevance
“…medical residents (MRs) [2]. MRs, indeed, can be frequently the first contact for patients, but they can lack knowledge and training about adoption of preventive measures [3–5]. Moreover, MRs who are in charge of the hospital patient care may play a key role in fostering appropriate preventive behaviors through the patients [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…medical residents (MRs) [2]. MRs, indeed, can be frequently the first contact for patients, but they can lack knowledge and training about adoption of preventive measures [3–5]. Moreover, MRs who are in charge of the hospital patient care may play a key role in fostering appropriate preventive behaviors through the patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Coley et al have supposed that the secondary attack rate among unprotected HCWs is higher (54.3%) respect to attack rate among adults (34.1%) [10]. Nonetheless, only few studies have been carried out about ILI incidence in MRs at both the local and national level [3]. The objective of this multicentre study were to assess the reported incidence of ILIs among Italian MRs during the 2011–2012 influenza season and to detect variables associated with ILI occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…In another published survey of residents during the pH1N1 pandemic, May et al 10 found that 59% of residents would wear gloves, 44% would wear a surgical mask, and 35% would wear an N95 respirator before entering the room of a patient with ILI. Although our respondents reported higher rates of adherence to the use of gloves (82%) and surgical mask or higher level of protection (83%-88% depending on the hospital), fewer responding physicians used other forms of required PPE that were not evaluated in the survey of May et al, including eye protection (36%) and gowns (58%).…”
Section: Discussionmentioning
confidence: 99%
“…Although our respondents reported higher rates of adherence to the use of gloves (82%) and surgical mask or higher level of protection (83%-88% depending on the hospital), fewer responding physicians used other forms of required PPE that were not evaluated in the survey of May et al, including eye protection (36%) and gowns (58%). 10 Lack of awareness of patients' pH1N1 or ILI status and unavailability of PPE near patient rooms were the most common reasons cited for not using recommended PPE. These findings demonstrate the importance of early identification of patients requiring isolation precautions and the administrative responsibilities of installing isolation precaution signage and ensuring the appropriate stock of supplies on each floor.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of the prescribers and dispensers indicated that H1N1/09 influenza was a serious health problem requiring educating the public on its prevention measures, none of them adopted preventive measures necessary during an air-borne disease outbreak. The lack of substantial change in adopting preventive measures or knowledge about the modes of H1N1 transmission among the health-care providers suggests that community mitigation measures for H1N1/09 influenza and other outbreaks are unlikely to succeed if health-care providers do not take the leading role [15,16].…”
Section: Discussionmentioning
confidence: 99%